2020
DOI: 10.1080/10408363.2020.1783198
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 pandemic

Abstract: In December 2019, an outbreak of pneumonia of unknown origin was reported in Wuhan, Hubei Province, China. Pneumonia cases were epidemiologically linked to the Huanan Seafood Wholesale Market. Inoculation of respiratory samples into human airway epithelial cells, Vero E6 and Huh7 cell lines, led to the isolation of a novel respiratory virus whose genome analysis showed it to be a novel coronavirus related to SARS-CoV, and therefore named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). SARS-CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
539
0
58

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,134 publications
(817 citation statements)
references
References 139 publications
1
539
0
58
Order By: Relevance
“…The emergence of SARS-CoV-2 and its route of viral transmission remain a mystery, but it is believed to have a zoonotic origin, likely in bats (Tang et al, 2020). In late December 2019, several patients in Wuhan, People's Republic of China were diagnosed with severe pneumonia of an unknown aetiology (Koh et al, 2020;Ciotti et al, 2020;Mü nnich et al, 1988;Bogoch et al, 2020). The virus has since spread rapidly around the world, infecting millions and killing hundreds of thousands (https://coronavirus.jhu.edu/ map.html).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of SARS-CoV-2 and its route of viral transmission remain a mystery, but it is believed to have a zoonotic origin, likely in bats (Tang et al, 2020). In late December 2019, several patients in Wuhan, People's Republic of China were diagnosed with severe pneumonia of an unknown aetiology (Koh et al, 2020;Ciotti et al, 2020;Mü nnich et al, 1988;Bogoch et al, 2020). The virus has since spread rapidly around the world, infecting millions and killing hundreds of thousands (https://coronavirus.jhu.edu/ map.html).…”
Section: Introductionmentioning
confidence: 99%
“…It was also identified that secondary or intermediate hosts in which SARS-CoV-2 lived prior to reaching humans were likely the pangolins [8]. After the sustained human-to-human transmission was identified and the virus was adapted to humans, international outbreaks of COVID-19 were reported in South Korea, Iran, and Italy and the virus then rapidly spread worldwide [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 has now spread to more than 210 countries across the globe, accounting for more than 0.85 million deaths out of 26 million confirmed cases reported till 2 nd September, 2020, and thus has created huge panic, havoc, and fear among worldwide population. Efforts to develop vaccines, drugs, therapies, immunomodulatory agents and strategies to enhance immunity against SARS-CoV-2 infection are continuously being made along with adopting appropriate mitigation strategies to safeguard the health of the humans and save their lives from COVID-19 pandemic [5][6][7][8][9][10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%